Tanggung Jawab Hukum Bagi Pekerja yang Tidak Melaksanakan Employee Branding - Permadi, Rangga Setya; Ambarwati, Mega Dewi (Media Hukum Indonesia (MHI), 2025)
In the context of industrial relations in Indonesia, employee branding plays an important role in shaping the company's image through employee behavior and attitudes. Employees have a responsibility to maintain the company's reputation in accordance with applicable laws and internal regulations. This article analyzes the legal framework governing employee branding obligations and the legal implications that may arise if employees violate these obligations. Based on normative analysis, it was found that violations of employee branding obligations can result in legal sanctions, both internal such as termination of employment (PHK) and administrative sanctions, and external such as claims for compensation. Thus, it is important for companies and employees to understand the obligations and consequences related to employee branding in employment relations.